Clinical significance of brachial flow‐mediated dilation in patients with rheumatoid arthritis. (18th January 2013) - Watanabe, Tsuneo; Takemura, Masao; Sato, Masao; Matsunami, Hidetoshi; Seishima, Mitsuru; Shimizu, Katsuji; Matsuoka, Toshio
Abstract Aim This study aimed to clarify whether different anti‐tumor necrosis factor (TNF) drugs can improve endothelial function better than conventional disease‐modifying anti‐rheumatic drugs (DMARDs) in a series of Japanese patients with rheumatoid arthritis (RA). Method Twenty‐five patients who met the American College of Rheumatology 1987 revised diagnostic criteria for RA were randomly selected for this study. The percentage of brachial flow‐mediated dilation (%FMD) and maximum carotid intima‐media thickness were examined by ultrasonography. Results The %FMD in the group treated with anti‐TNF therapy was significantly higher than that in the group treated with DMARDs (P < 0.001). The %FMD was significantly correlated with anti‐TNF therapy (r = 0.684, P < 0.001) and Disease Activity Score C‐reactive protein (r = –0.404, P < 0.05). Multiple regression analysis revealed that anti‐TNF therapy was significantly associated with %FMD (β = 0.684, P < 0.001). Conclusion Anti‐TNF therapy may influence endothelial function more than conventional DMARD therapy. Prospective longitudinal studies examining whether anti‐TNF therapy was able to improve endothelial function are required.